2021
DOI: 10.2147/idr.s301318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Clinical Characteristics and Changes of Antibiotic Resistance in Children with Nontyphoidal Salmonella Infections from 2009–2018 in Chongqing, China

Abstract: Purpose Nontyphoidal Salmonella (NTS) is a leading bacterial cause for acute gastroenteritis in children. With the increasing use of antibiotics worldwide, antibiotic resistance has become a global problem. However, data on NTS infections and changes in antibiotic resistance among children remain limited in China. We aimed to characterize the prevalence, clinical feature, serotype and the changes of antibiotic resistance of NTS in children in Chongqing. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Typhimurium and its monophasic variant and S . Enteritidis were the most common serotypes found among patients with diarrhea, consistent with some studies in other areas of China ( Zhan et al, 2017 ; Liu et al, 2021 ; Wu L. J. et al, 2021 ). However, S .…”
Section: Discussionsupporting
confidence: 90%
“…Typhimurium and its monophasic variant and S . Enteritidis were the most common serotypes found among patients with diarrhea, consistent with some studies in other areas of China ( Zhan et al, 2017 ; Liu et al, 2021 ; Wu L. J. et al, 2021 ). However, S .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Wu et al showed the dominance of S . Typhimurium (79.2%) among isolates recovered from children with NTS infections between 2009 and 2018 in Chongqing, China ( 58 ). Another Chinese study carried out in the Conghua district of Guangzhou, between June and October 2020 isolated S .…”
Section: Discussionmentioning
confidence: 99%
“…The common resistance was observed against cefazolin (1st generation of cephalosporin), streptomycin (aminoglycoside), ampicillin (penecillins), the combination of ampicillin-sulbactam, doxycycline and tetracycline (tetracyclines), and levofloxacin (quinolones). The high resistance to these categories has becoming frequently observed in Salmonella isolates recovered from food, human, and animal samples ( 6 , 19 , 25 , 26 , 58 , 62 ). Moreover, we reported a high incidence of MDR among isolates (83.91%) which was higher than that found in Salmonella recovered from hospitalized patients in the Conghua district of Guangzhou, China (47.06%) ( 59 ), and from children with NTS infections in Chongqing, China (13.7%) ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, non-typhoid Salmonella is emerging as one of the main pathogens in infants in China, causing diarrhea, fever and abdominal pain (26)(27)(28)(29). Children have immature immune systems and weak gastrointestinal systems that are Table V.…”
Section: Discussionmentioning
confidence: 99%